Mapping the Social and Organizational Dimensions of Accounting: A Systematic Literature Review and Bibliometric Analysis - Ismail, Susanty; Niswatin, Niswatin; Amaliah, Tri Handayani (Publikasi Indonesia, 2026)
This research maps the social and organizational dimensions of accounting research through a systematic literature review (SLR) combined with bibliometric analysis. Drawing on 196 peer-reviewed articles indexed in Scopus and published between 2019 and 2024, the study examines how accounting operates as a social practice embedded in power relations, institutional arrangements, governance structures, and professional work. Following PRISMA-based screening procedures, the dataset was analyzed using VOSviewer to identify thematic clusters, keyword co-occurrence patterns, and intellectual structures within the literature. The analysis reveals six dominant research streams: (1) crisis and organizational resilience, (2) public sector governance and control, (3) critical accounting and power relations, (4) institutional logics and sustainability, (5) global standards and translation processes, and (6) professional work and auditing practices. The findings demonstrate a strong shift away from positivist approaches toward sociologically informed perspectives, with critical and institutional theories increasingly shaping accounting scholarship. By synthesizing fragmented debates across these clusters, this study contributes a structured overview of contemporary sociological accounting research and identifies future research agendas to advance theory, context-sensitive inquiry, and methodological pluralism in accounting studies.